Effects of Growth Hormone on the Differentiation of Mouse B-Lymphoid Precursors - Kiminobu Sumita; Naoki Hattori; Chiyoko Inagaki (Elsevier, 2005)
Growth hormone (GH) has been known to enhance immune responses directly or through insulin-like growth factor-I (IGF-I). The present study aimed to clarify the roles of GH in the differentiation of B-lineage precursors. In short-term bone marrow cultures, which contained stem cells and early B-lineage cells, GH (10 μg/L) treatment for one day decreased the percentages of stem cells (0.5-fold) and increased those of B-lineage cells (1.4-fold). Furthermore, GH changed the expressions of transcription factors for B cell progenitors differentiation such as paired box gene-5 (Pax-5), immunoglobulin-associated-α (Ig-α)/CD79a, Ig-β/CD79b, and IGF-I. Thus, a physiological concentration of GH stimulated the differentiation of B-lymphoid precursors from bone marrow stem cells. Since mRNAs of both GH and GH receptor were present in stem cells and B-cell precursors in bone marrow, GH may modulate B-lymphoid precursors development in an autocrine or paracrine manner in bone marrows. Keywords:: growth hormone, bone marrow, stem cell, B cell, insulin-like growth factor-I